The leading-edge manager's guide to success : strategies and better practices - Parmenter, David (Hoboken, N. J. : Wiley, 2011)
'Practical, commonsense advice on becoming an effective leader Examining the baggage that most managers have and then helping them to understand the personal traits that can limit their potential, this book guides you through the pathway of self development, then takes you through management and leadership better practices, providing many implementation tools. All you need to know when getting prepared for a'management role'. How to develop'conquest leadership' attributes. Traits to make you a'winning' CEO. Latest thinking on KPIs, quarterly rolling planning, decision based reporting and performance related pay. How to create Winning Management and Leadershp Habits. Examines how to become More Financially Aware. This book is a very practical guide with templates,'how to do it tools', stories about gifted leaders, checklists and examples and is devoid of all intellectual arguments on management. With directional guidance on what managers need to know in order to be able to manage and lead others, The Leading-Edge Manager's Guide to Success helps managers and'managers to be' as they climb the'management mountain.''--
Includes bibliographical references and index.
Keywords: Executive ability; Management; Leadership; Success in business